In vivo analysis of bovine colostrum whey-caseinate nanoparticles using rat model: Bio accessibility of immunoglobulins - Muhammad Umar; Uracha Rungsardthong Ruktanonchai; Davids Makararpong; Natchanon Rimsueb; Anil Kumar Anal (Future Foods)
The colostrum whey-sodium caseinate nanoparticles (NPs) were prepared with a diameter <200 nm and zeta potential of -21.4 which indicate the stability of NPs. The powder samples were fed to rats for 2 weeks to evaluate the effect on the Igs concentration in blood serum. The fabricated NPs showed significant increment (p < 0.05) in Igs concentration levels in the blood due to their good efficacy in protecting the Igs from gastric digestion. The hydrophobic regions were buried inside the protein network during gastric digestion which restricted the enzyme activity. The concentration of Igs increased significantly (p < 0.05) due to NPs, IgG was increased to 9.33 μg/mL and 9.50 μg/mL, IgA was increased to 1.69, and 1.70 μg/mL and IgM was increased 1.55 and 1.60 μg/mL for NPs-1 and NPs-2 groups respectively. However, colostrum contains some amount of lactose and other glycoproteins which protect the digestion of Igs in the gastric phase as compared to whey protein which shows a slightly lower level of Igs. Morphological changes indicated that the NPs were coagulated in the stomach due to pH sensitive caseinate which protected the Igs degradation. These powders can be utilized as a good source of bioactive Igs from bovine colostrum with improved functionality and digestibility.